The income sources of single parents: A comparative analysis - Mia Hakovirta (Luxembourg Income Study (LIS), 2001)
The aim of this article is to examine the different income sources of single parents using the method of the income packages. The concept of income package highlights the importance of both the source and the level of income of single parent families in different welfare states. These potential sources of income are central when analyzing the nature of support offered by the welfare state to single parents. This article attempts to give answer to the following questions: 1. Is it the case that the degree to which single parents participate in paid employment influences their income packages? In those countries where paid employment is common among single parents, is the main component of their income packages income from work? In contrast, in those countries where paid employment is rare among single parents, are incomes mainly derived from social transfers? 2. How has the income sources of single parents changed during the economic downturn in some countries during the 1990s? Has the dependency on state benefits increased and the amount of income from employment decreased as a result of a weakened labor market position among single parents? The study focuses on the turn of the decade (namely 1983-86 and 1991-95) when social policy was reformed in many countries. The countries selected for this study are Australia, Britain, the US, the Netherlands, Germany, Norway, Finland and Denmark. The article starts with an overview of the different work requirements of single parents across countries. This serves as a platform for empirical analysis on income packages. Then the changes in labor market participation rates of single parents are studied. This is followed by a study of the income packages and income levels of single parents. The article concludes with a discussion of the main research findings.
Keywords: 330; Alleinerziehende; Unterhaltsrecht; Lohn; Familienleistungsausgleich; Öffentliche Sozialleistungen; OECD-Staaten